Otaku Dadakan: Studi Kasus Penggemar Anime One Piece di Kalangan Mahasiswa - Muh. Nur Rahmat Yasim (Universitas Muslim Maros, 2022)
nime (Japanese animation) which currently become popular in the community has resulted in the emergence of various anime products, such as action figures, posters, comics, and even animated films. One of the most popular anime is One Piece, and its rabid fans are known as anime otaku. This anime otaku phenomenon not only occurs in Japan, but also throughout the world, including Indonesia. This article deals with newcomers who are interested in popular anime, and call themselves otaku, labeled as impromptu otaku by anime otaku. Using a qualitative approach, this research was conducted through social media Instagram and TikTok. The research informants were ten students, who came from public and private universities in the city of Makassar. They consist of six men and four women, whose age range between 19 and 25 years. Data was collected using in-depth interview and observation techniques. One Piece is one of the anime that has a high rating and is the most popular anime of all time. For impromptu otaku, this is considered as “the king of anime